THE GEORGE W. LA BORDE COLLECTION OF ROMAN AUREI - Giovanni Gorini (Journal of Ancient History and Archaeology, 2017)
The George W. La Borde Collection of Roman Aurei - Part I, Numismatica Ars Classica NAC AG, Zürich - London, 23 May 2016